Effect of Glass Powder on Physical and Mechanical Properties of Reactive Powder Concrete (RPC) - Ardiansyah, Ardiansyah; Sutandar, Erwin; Supriyadi, Asep (Jurnal Teknik Sipil, 2024)
Glass waste is often dumped directly into the ground or rivers in large quantities, causing environmental pollution. To overcome this problem, glass waste can be processed into powder as a mixture in concrete. This research partially uses glass powder to replace silica fume in reactive powder concrete. This research uses experimental methods to test concrete's physical and mechanical properties. The research process includes making test specimens, analyzing materials, curing, testing slump, compressive strength, split tensile strength, and elasticity modulus. The results showed that the slump values ranged from 50-75 mm, with an average volume weight of 1.990,073 kg/m ³ - 2.149,228 kg/m ³. The average compressive strength values were in the range of 56,277 MPa "“ 56,341 MPa, the average split tensile strength between 8,182 MPa - 9,384 MPa, and the average elasticity modulus between 30.543,305 MPa "“ 32.568,181 MPa. This research found that glass powder can partially replace silica fume, with an optimum content of 12,5%. At this level, the average compressive strength of RPC concrete at 28 days reached 66,341 MPa. Therefore, using glass powder in RPC concrete mixes can improve the quality of the concrete and become a more environmentally friendly construction solution.